Language, social, and executive functions in high functioning autism: a continuum of performance. - Landa RJ; Goldberg MC (Journal of Autism & Developmental Disorders, 2005)
This study examined language and executive functions (EF) in high-functioning school-aged individuals with autism and individually matched controls. Relationships between executive, language, and social functioning were also examined. Participants with autism exhibited difficulty on measures of expressive grammar, figurative language, planning, and spatial working memory. A mixed profile of impaired and enhanced abilities was noted in set-shifting. While controls showed the typical increase in errors when shifting sets from an intra-dimensional to an extra-dimensional stimulus, this pattern was not noted in participants with autism. Relationships between EF, language, and social performance were weak to non-existent. Implications for theories of core deficit in autism and dissociable nature of the language and executive impairments in autism are discussed.